The effectiveness of implementing a Behaviour Based Safety approach in accident prevention. A case study of Delta Beverages, Lagers Manufacturing Company, Harare. - Chimombe, Leandrah (Midlands State University, 2017)
The main goal of the study was to assess the effectiveness of implementing a Behaviour Based Safety (BBS) approach in accident prevention in manufacturing industries of Zimbabwe with focus on Delta Beverages, Lagers Manufacturing in Harare. Causes of most occupational related accidents were identified, Behaviour Based safety measures being taken in accident prevention at Delta Lagers were also taken note of as well as legislative and policy issues related to Behaviour Based Safety. To further establish a robust research, an analysis of relationships identified during the study was employed through chi-square tests. Both qualitative and quantitative methods were employed through the use of questionnaires, interviews and direct observations in order to establish a comprehensive research. The research established that both unsafe conditions and unsafe behaviours largely contribute to occurrence of occupational related accidents but with unsafe behaviours being the greatest contributor. The Behaviour Based Safety measures being taken in accident prevention at Delta Lagers such as issuing of violation forms and offering Safety, Health and Environment incentives have so far assisted in reducing unsafe acts although management support is still lacking in driving these safety related issues. The research also divulged that the legislation of Zimbabwe does not fully incorporate behavioural management as a measure to curb accident occurrence. Thus recommendations brought forward were the need to incorporate behavioural management as atool to assist accident prevention in the legal framework of Zimbabwe, also the need to formally adopt the Behaviour Based Safety approach in accident prevention at Delta Lagers and for employees to be given the right to refuse to work under unsafe conditions among others.